ANALISIS TREN IKLIM DAN KETERSEDIAAN AIR TANAH DI PALEMBANG, SUMATRA SELATANCLIMATE AND SOIL WATER TRENDS ANALYSIS FOR PALEMBANG REGION, SOUTH SUMATRA - Muh Taufik (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
Long-term climate trend is being one of greatest research interests amongst climate scientists around the world to see whether climate change occurs or not at local, regional or global scale. However, only a few studies are available that discusses trend of climate extreme in equatorial climate, Indonesia. This paper tries to analyze climate trend and its impact to water availability in Palembang region using daily rainfall and air temperature data for the year of 1984-2009. Trend analysis was performed using Mann-Kendall test at α equal to 5%. We found that daily air temperature indicated that the rise of maximum, average, and minimum temperatures has occurred with statistically significant changes during the observation period. However, daily temperature range did not significantly change. We didn’t find any significant change for rainfall predictors except the number of rainfall event that significantly showed a decrease trend. With a simple water balance, we calculated monthly soil water content indicating that its’ decline was statistically significant (α=5%). With these findings, we have not made a conclusion whether climate change occurred or not yet, until influence of local effect such as urban heat island clearly explained.Long-term climate trend is being one of greatest research interests amongst climate scientists around the world to see whether climate change occurs or not at local, regional or global scale. However, only a few studies are available that discusses trend of climate extreme in equatorial climate, Indonesia. This paper tries to analyze climate trend and its impact to water availability in Palembang region using daily rainfall and air temperature data for the year of 1984-2009. Trend analysis was performed using Mann-Kendall test at α equal to 5%. We found that daily air temperature indicated that the rise of maximum, average, and minimum temperatures has occurred with statistically significant changes during the observation period. However, daily temperature range did not significantly change. We didn't find any significant change for rainfall predictors except the number of rainfall event that significantly showed a decrease trend. With a simple water balance, we calculated monthly soil water content indicating that its' decline was statistically significant (α=5%). With these findings, we have not made a conclusion whether climate change occurred or not yet, until influence of local effect such as urban heat island clearly explained.